2019
DOI: 10.14309/01.ajg.0000613096.52383.35
|View full text |Cite
|
Sign up to set email alerts
|

P032 Does Patient Knowledge Affect Anxiety, Depression, and Quality of Life in Patients With Inflammatory Bowel Disease?

Abstract: BACKGROUND: Disease specific knowledge amongst inflammatory bowel disease (IBD) patients remains lacking. Our study aims to (1) determine the extent of disease specific knowledge amongst IBD patients in Lebanon and (2) determine the impact of patient knowledge on anxiety, depression, and quality life while controlling for disease activity. METHODS: We prospectively recruited adult IBD patients from the GI clinic at a tertiary referral center in Beirut, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Having awareness about COVID-19 is not necessarily able to reduce anxiety. Previous research ndings suggest that understanding of IBD (In ammatory Bowel Disease) was not found to be related to anxiety (Hosni et al, 2019) although in other studies found otherwise (Panayiotou et al, 2018). Individuals who have more understanding of IBD knowledge have a tendency to have more anxiety.…”
Section: Data Collection Uses a Likert Scale Consisting Of The Awarenmentioning
confidence: 86%
“…Having awareness about COVID-19 is not necessarily able to reduce anxiety. Previous research ndings suggest that understanding of IBD (In ammatory Bowel Disease) was not found to be related to anxiety (Hosni et al, 2019) although in other studies found otherwise (Panayiotou et al, 2018). Individuals who have more understanding of IBD knowledge have a tendency to have more anxiety.…”
Section: Data Collection Uses a Likert Scale Consisting Of The Awarenmentioning
confidence: 86%